In Vivo Posterior Cruciate Ligament Elongation in Running Activity after Anatomic and Non-anatomic Anterior Cruciate Ligament Reconstruction - Tang, Jing (Knee Surg Sports Traumatol Arthrosc, 2016)
PURPOSE: The goals of this study were to (1) investigate the in vivo elongation behavior of the posterior cruciate ligament (PCL) during running in the uninjured knee; and (2) evaluate changes in PCL elongation during running after anatomic or non-anatomic anterior cruciate ligament (ACL) reconstruction. METHODS: Seventeen unilateral ACL-injured subjects were recruited after undergoing anatomic (n=9) or non-anatomic (n=8) ACL reconstruction. Bilateral high-resolution CT scans were obtained to produce 3D models. Anterolateral (AL) and posteromedial (PM) bundles insertion sites of the PCL were identified on the 3D CT scan reconstructions. Dynamic knee function was assessed during running using a Dynamic Stereo X-ray (DSX) system. The lengths of the AL and PM bundles were estimated from late swing through mid-stance. The contralateral knees served as normal controls. RESULTS: Control knees demonstrated a slight decrease in AL bundle, and a significant decrease in PM bundle length following foot strike. Length and elongation patterns of the both bundles of the PCL in the anatomic ACL reconstruction group were similar to the controls. However, the change in dynamic PCL length was significantly greater in the non-anatomic group than in the anatomic reconstruction group after foot strike (P<0.05). CONCLUSION: The AL bundle length decreased slightly and the PM bundle length significantly decreased after foot strike during running in uninjured knees. Anatomic ACL reconstruction maintained normal PCL elongation patterns more effectively than non-anatomic ACL reconstruction during high-demand, functional loading. These results support the use of anatomic ACL reconstruction to achieve normal knee function in high-demand activities. LEVEL OF EVIDENCE: Case-control study, Level III